Blood–Brain Barrier Disruption and Hemorrhagic Transformation in Acute Ischemic Stroke: Systematic Review and Meta-Analysis - Arba, Francesco; Rinaldi, Chiara; Caimano, Danilo; Vit, Federica; Busto, Giorgio; Fainardi, Enrico (Frontiers in Neurology, 2021)
Introduction: Hemorrhagic Transformation (HT) is a complication of reperfusion therapy for acute ischemic stroke. Blood-Brain-Barrier (BBB) disruption is a crucial step towards HT, however, in clinical studies there is still uncertainty about this relation. Hence we conducted a systematic review and meta-analysis to summarize the current evidence. Methods: Systematic review and meta-analysis of observational studies from January 1990 to March 2020 about the relation between BBB disruption and HT in patients with acute ischemic stroke with both Computed Tomography (CT) and Magnetic Resonance (MR) assessment of BBB. The outcome of interest was HT at follow-up imaging evaluation (within 48 hours from symptoms onset). We pooled data from available univariate odds ratios (ORs) in random-effects models with DerSimonian-Laird weights and extracted cumulative ORs. Results: We included 30 eligible studies (14 with CT and 16 with MR), N=2609 patients, with 88% and 70% of patients included in CT and MR studies treated with acute stroke therapy, respectively. The majority of studies were retrospective and had high or unclear risk of bias. BBB disruption was measured with consistent methodology in CT studies, whereas in MR studies there was more variability. All CT studies provided a BBB disruption cut-off predictive of HT. Four CT and ten MR studies were included in quantitative analysis. We found that BBB disruption was associated with HT with both CT (OR=3.42; 95%CI=1.62-7.23) and MR (OR=9.34; 95%CI=3.16-27.59). There was a likely publication bias particularly for MR studies. Conclusion: Our results confirm that BBB disruption is associated with HT in both CT and MR studies. Compared to MR, CT has been more uniformly applied in the literature and has resulted in more consistent results. However, more efforts are needed for harmonization of protocols and methodology for implementation of BBB disruption as a neuroradiological marker in clinical practice.